Therapeutic effects of mesenchymal stromal cells transplantation in animal models of chronic obstructive pulmonary disease: a systematic review and meta-analysis of emphysema and lung inflammation models - Zhao, Yuan; Zhou, Shuhui; Pei, Juan; Meng, Ying; Zhang, Zhengyi (Frontiers in Cell and Developmental Biology, 2026)
ObjectiveChronic obstructive pulmonary disease (COPD) presents core pathological changes that current medications cannot reverse. Mesenchymal stromal cell (MSC) transplantation has shown therapeutic potential in preclinical studies; however, significant heterogeneity and inconsistency exist in animal experiments simulating key COPD pathologies (such as emphysema and inflammation) based on acute injury models. We aim to systematically evaluate the efficacy of MSC transplantation in animal models simulating COPD pathology through a meta-analysis and to explore the impact of key strategies such as administration routes and dosages on efficacy.MethodsA systematic search was performed in PubMed, Web of Science, Embase, and Scopus databases (up to 1 July 2025) to identify randomized controlled trials (RCTs) involving MSC transplantation in animal models of simulated COPD pathology. Risk of bias was assessed using the SYRCLE tool, and meta-analysis was conducted using R software.ResultsA total of 40 studies were included. The meta-analysis revealed that MSC transplantation significantly improved alveolar structural damage compared to control groups (MLI: SMD = −2.84, 95% CI: 3.22 to −2.45), increased anti-inflammatory IL-10 levels (SMD = 6.54, 95% CI: 2.08–11.00), reduced pro-inflammatory TNF-α levels (SMD = −1.61, 95% CI: 2.72 to −0.5), and significantly inhibited pulmonary tissue cell apoptosis (SMD = −4.06, 95% CI: 5.71 to −2.41). Subgroup analysis showed that intratracheal transplantation was more effective than intravenous transplantation in improving MLI, enhancing IL-10 levels, and reducing apoptosis. Moreover, the therapeutic effects were dose-dependent, with higher doses (≥5 × 106) generally yielding superior outcomes. Publication bias assessment for MLI suggested potential bias; however, the adjusted combined effect size remained statistically significant, confirming the robustness of the conclusion that MSCs significantly improve alveolar structure.ConclusionMSC transplantation exerts multiple therapeutic effects by alleviating emphysema, regulating inflammatory balance, and inhibiting cell apoptosis. The study further identifies intratracheal delivery and higher cell dosages as promising optimization strategies for MSC transplantation. These findings provide critical references for the standardized design of future preclinical studies and the selection of parameters for subsequent clinical trials, while the differences in disease progression between animal models and human conditions remain key factors to consider for future clinical translation.